The Effect of Cost Drivers, Activity Volume and Overhead Rates on Activity-Based Product Costing at CV. XYZ Food Sidoarjo - Fitri , Pipit Fadilatul; Prawira , Anggun Wida; Prasetiya, Okta Antika; Carollina, Riska (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to examine and analyze the influence of cost drivers, activity volume, and overhead rates on activity-based product cost determination at CV. XYZ Food Sidoarjo. The research applies a quantitative explanatory approach, utilizing secondary data from financial statements and production activity reports over the period 2016–2024. Data analysis is conducted using multiple linear regression, preceded by classical assumption tests to ensure model validity. The results indicate that, partially, cost drivers and activity volume significantly affect product costs, while overhead rates do not show a significant effect. However, simultaneously, all three variables have a significant influence on product cost determination. These findings highlight the importance of accurately identifying cost drivers and managing activity volumes within the Activity-Based Costing (ABC) system to achieve cost efficiency and accurate product pricing. Recommendations for CV. XYZ Food include enhancing activity data collection systems, conducting regular evaluations of overhead rates, and integrating ABC methods into strategic decision-making processes. The managerial implication emphasizes the need for controlling cost-generating activities and improving production process efficiency as part of data-driven financial planning.